2011
DOI: 10.1186/ar3250
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dsDNA-NcX ELISA: dsDNA-loaded nucleosomes improve diagnosis and monitoring of disease activity in systemic lupus erythematosus

Abstract: IntroductionThe objective of this study was to compare the clinical usefulness of the new anti-double-stranded DNA nucleosome-complexed enzyme-linked immunosorbent assay (Anti-dsDNA-NcX ELISA), which is based on dsDNA-loaded nucleosomes as antigens, with established test systems based on dsDNA or nucleosomes alone for systemic lupus erythematosus (SLE) diagnostics and determination of disease activity.MethodsSera from a cohort of 964 individuals comprising 207 SLE patients, 357 disease controls and 400 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
(33 reference statements)
3
24
0
1
Order By: Relevance
“…Erythrocyte-bound C3 and C4 reflect DA cross-sectionally and longitudinally nearly as well as serum levels of complement C3 and C4 6. We and others have found that antibodies against nucleosomes7 8 and dsDNA-complexed nucleosomes (Anti-dsDNA-NcX ELISA) may be more useful for monitoring DA than traditional anti-dsDNA antibodies 9…”
Section: Introductionmentioning
confidence: 93%
“…Erythrocyte-bound C3 and C4 reflect DA cross-sectionally and longitudinally nearly as well as serum levels of complement C3 and C4 6. We and others have found that antibodies against nucleosomes7 8 and dsDNA-complexed nucleosomes (Anti-dsDNA-NcX ELISA) may be more useful for monitoring DA than traditional anti-dsDNA antibodies 9…”
Section: Introductionmentioning
confidence: 93%
“…12,13 The most commonly used marker autoantibodies in SLE react with dsDNA, Smith (Sm) antigen, nucleosomes and ribosomal P proteins. 14,15 Antinucleosome antibodies occur in SLE at a frequency of 60%-100 %. 16 The frequency range may be influenced by factors like ethnicity, disease duration, disease activity and treatment.…”
Section: Diagnostic Utilitymentioning
confidence: 99%
“…17 Interestingly, ELISAs using the strong adhesive property of nucleosomes (instead of commonly used linkers like methylated albumin, protamine sulfate or poly-L-lysine) to attach dsDNA to the plate, showed even higher diagnostic performance in SLE, and outperformed even the Farr assay. 14 …”
Section: Diagnostic Utilitymentioning
confidence: 99%
“…Bu testler arasında duyarlılık ve özgüllük açısından büyük farklar mevcuttur ve özellikle de antidsDNA ELISA'nın farklı ticari kitleri arasında bu fark belirgindir (11). ELISA testi ile çalışılan anti-dsDNA sonuçları IgG spesifik CLIF veya Farr RIA yöntemleri ile doğrulanmalıdır (12,13 …”
unclassified